Land Boundary Disputes Resolution: A Qualitative Study of Peace and Conflict Resolution between Erinle-Offa Communities in Kwara State, Nigeria - Bamidele, Seun; Idowu, Olusegun Oladele (ABUAD Journal of Social and Management Sciences, 2023)
The study focused on land boundary disputes and the resolution challenges in the Erinle-Offa communities of Kwara State, Nigeria. The history of the two communities is laced with hostility and aggression, which has resulted in violent disputes at various times. Quite a number of works have emerged on the causes and consequences of the violent clash. However, the aftermaths of the dispute, especially the tense relationship and peacebuilding process in the area, are yet to be sufficiently interrogated. This study investigated the state of relations between Erinle and Offa as well as land dispute resolution processes in the locality involving complex actors after the last violent clash. It also examined the factors responsible for land boundary disputes between the two communities. The findings showed that negative peace currently exists in the two communities and the land conflict is a perennial one that could arise at any time. The study used both primary and secondary data. The main method of data collection was the unstructured interview, which was conducted with 120 people, made up of traditional rulers, and local, political, religious and youth leaders. Secondary data was sourced from texts, newspapers, magazines, official gazettes, archival materials and the Internet.